Customer satisfaction through market orientation: empirical investigation of the three market oriented components - Vaikunthavasan, S. (University of Jaffna, 2016)
As today's organizations have to react to customer and competitors and then to manage their own resources and capabilities. This study examines the effect of market orientation components on customer satisfaction of food restaurants in Jaffna district. The model was tested using data collected from 60 food restaurants and 600 major customers in Jaffna district by using questionnaire. The findings illustrated the effects of the three components of market orientation within Food restaurant firms as customer orientation, competitor orientation and inter functional coordination influence on customer satisfaction. This research consider the resource dependency theory, and Firms have major concern to create customer value through adopting and anticipating developments with available resources and capabilities. It provided managerial implications to food restaurant on market oriented implementation strategies. Further firms understand retaining customers are very important and customers can easily switch to competitive restaurants. Having proper inter-functional coordination base on resource with consideration of customers and competitors leads to success and survival of firms. Overall, high levels of customer orientation, competitor orientation and inter functional coordination for food restaurants are healthy, the findings also reveal that if every functional unit in a restaurant is wide and major minded with their sole intention for dealing with customers to reap sustainable satisfaction.
Keywords: Competitor orientation; Customer orientation; Customer satisfaction; Inter functional coordination; Market orientation